2022
DOI: 10.3389/fpsyg.2022.915479
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience and Career Success of Female Nurses in Central China: The Mediating Role of Craftsmanship

Abstract: BackgroundNurses’ career success is an important factor affecting the quality of nursing services and the stability of the nursing workforce, and enhancing nurses’ career success level is of key significance to the development of the nursing discipline. As psychological resilience and craftsmanship are important spiritual traits in the process of nurses’ career development, it is important to understand the mechanism of their effects on nurses’ career success level.ObjectiveTo explore the current situation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A study examining the effect of the psychological resilience of emergency nurses on their thanatophobic behaviours determined that nurses had moderate psychological resilience [22]. There are studies in the literature showing that nurses' psychological flexibility of nurses working in different departmentsis moderate [31,32]. Resent research is coherent with other studies in the literature.…”
Section: Discussionmentioning
confidence: 58%
“…A study examining the effect of the psychological resilience of emergency nurses on their thanatophobic behaviours determined that nurses had moderate psychological resilience [22]. There are studies in the literature showing that nurses' psychological flexibility of nurses working in different departmentsis moderate [31,32]. Resent research is coherent with other studies in the literature.…”
Section: Discussionmentioning
confidence: 58%
“…Duan et al (2021) shows that craftsmanship spirit is associated with high organizational resilience. It is also found that craftsmanship has positive effect on several individual outcomes, including personal initiative ( Gao, 2022 ), well-being ( Li et al, 2021 ), and career success ( Xue et al, 2022 ). Given the importance of craftmanship spirit, scholars naturally generate interest in exploring its antecedents.…”
Section: Introductionmentioning
confidence: 99%
“…Today, with the development of the times and the improvement of medical level, people's pursuit of high‐quality health is becoming more and more urgent, which brings greater challenges to the medical and health field. As the largest component of the healthcare system, the nursing group plays an important role in the sustainable development of human health (Mousavi et al, 2019; Xue et al, 2022). As the guardians of human health, nurses serve the public's life and death, and play an irreplaceable role in preventing illness, promoting healings and alleviating sufferings (Shah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%